"Just How Much Diversity Will the Law Permit?": The Americans with Disabilities Act, Diversity and Disability in Higher Education - Shallish, Lauren (Disability Studies Quarterly, 2015)
Civil rights laws including the Civil Rights Act of 1964, Title IX of 1972, Section 504 of the Rehabilitation Act of 1973 and the Americans with Disabilities Act of 1990 worked to protect classes and individuals for whom discrimination had been documented. In an effort to further remedy educational inequality, colleges and universities increasingly used identity categories to enable access and participation in postsecondary life. In addition to anti-discrimination statutes, attention to marginalized groups evolved to include larger networks of academic and co-curricular support such as formations of identity centers, cultural events, fields of study and scholarships yet disability is largely absent from this work as much of higher education maintains a singular focus on legal compliance. This study investigates how disability law is conceived and enacted on five divergent campuses and how participants understood both the function of disability law and other cultural, social and political aspects of disability-related identities.